Lower pole obstructive megaureter of duplex kidney: an exception to the Weigert-Meyer rule - I. M. Kagantsov; E. A. Kondrateva; S. A. Karavaeva; A. A. Sukhotskaya; M. V. Saliev; V. V. Sizonov (Вестник урологии, 2022)
Introduction. Anatomical features of the urinary tract in patients with duplicate kidneys are described using the Weigert-Meyer rule, since the orifice of the upper ureter has an ectopic location (inferomedial) and the orifice of the lower ureter has an orthotopic location (superolateral). However, there are rare cases of violation of this rule, complicated by obstructive megaureter, ectopic ureteral orifice, the presence of ureterocele.Objective. To report the rare clinical case of a lower pole obstructive megaureter as a violation of the Meyer-Weigert rule in the patient with complete ureteral duplication and to describe the use of ureteroureterostomy as an effective and safe method of surgical correction of the presented anomaly.Clinical case. We present a case of the infant (5 months old) with a lower pole obstructive megaureter. This pathology was identified through intravenous urography and voiding cystourethrography. Laparoscopic proximal end-to-side ureteroureteroanastomosis was chosen as a surgical treatment. Postoperative control intravenous urography showed the effectiveness (a reduction in the lower pole collecting system of the duplex kidney was revealed) and the safety of this method of correction.Conclusion.  There are only several clinical cases about exceptions to the Weigert-Meyer rule reported in literature, and most of them are about adult patients. The main surgical method of treatment in such cases is heminephrectomy. To our knowledge, this is the only reported case of using ureteroureterostomy in the patient with a lower pole obstructive megaureter. This technique has shown its effectiveness and safety for restoring the patency of the urinary tract, confirmed during the control postoperative examination.